PENGARUH STORE ATHMOSPHERE DAN STORE LOCATION TERHADAP IMPULSE BUYING PADA U.D SYAFA MARWA - Rangga, Muhammad; Heriyanto, Meyzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine the influence of store athmosphere and store location towards impulse buying on U.D Syafa Marwa. The sample in this study were taken 100 respondents and the technique used accidental sampling. The data in this study used survey method through questionnaires filled by consumers.The data obtained of questionnairetested through SPSS 21.0 program. The results of analysis used multiple linear regression analysis, determination test (R2 ), individual significance test (t test) and simultaneous significance test (F test) so it can be seen that store athmosphere variable had a positive effect on consumer impulse buying variable, stor location variable influences variable impulse buying, and a significant influence between store athmosphere and store location variables on impulse buying. The results shows R Square is the coefficient of determination and obtained R Square value of 0.700. That is, store athmosphere and store location affect impulse buying by 70%. Key Words : Store Athmosphere, Store Location, and Impulse Buying